“Sometimes Banning Abortion Doesn't Mean Fewer Abortions or Fewer Babies Die - It Just Means More Women Die”: A Thematic Analysis of Roe v. Wade Partisan Cable News Coverage - Trifiro, Briana Marie (AoIR Selected Papers of Internet Research, 2026)
This study examines the narratives constructed by partisan cable news outlets—CNN, MSNBC, and Fox News—in their coverage of the 2022 repeal of Roe v. Wade. Using a thematic analysis, the study identifies and analyzes recurring themes, storytelling elements, and moral evaluations that shaped these outlets’ portrayals of identity groups such as women, children, Republicans, and Democrats. The analysis explores how narratives were strategically deployed to align with each outlet’s ideological stance, offering insight into how media frames contentious social issues to reinforce partisan perspectives.The findings reveal distinct narrative patterns across outlets. CNN and MSNBC emphasized themes of bodily autonomy and healthcare, portraying women as central victims of restrictive abortion policies. These outlets framed abortion as a critical aspect of women’s rights, often highlighting the societal harms caused by the repeal. Fox News, in contrast, emphasized moral evaluations and traditional values, portraying Republicans as protectors of unborn children and casting Democrats as moral adversaries. This outlet frequently used narratives centering on the sanctity of life, aligning with a broader conservative agenda.Through its focus on storytelling elements such as characterization, plot development, and thematic cues, the study demonstrates how partisan media constructs narratives to engage audiences and influence public discourse. These findings contribute to the sociological understanding of how media narratives shape collective identities, reinforce ideological divides, and frame debates on contentious societal issues. This research underscores the critical role of storytelling in contemporary media ecosystems and highlights the need for further exploration of its sociopolitical implications.